A two-scale model for simultaneous sintering and crystallization of glass-ceramic scaffolds for tissue engineering - Huang, R.; Pan, J.; Boccaccini, Aldo R.; Chen, Q. Z. (Acta Biomaterialia, 2008)
Bioglass®-based glass-ceramic foams have been developed recently as highly porous, mechanically competent, bioactive and degradable scaffolds for bone tissue engineering. However, the development of the material so far has been based on a trial-and-error approach, and the existing materials are far from being optimized. In this paper, a mechanism-based model is presented for sintering deformation of Bioglass® foams. The porous foams consist of struts which, in turn, consist of Bioglass® particles. A corresponding two-scale model is developed based on existing viscous sintering models. Crystallization plays a key role in the sintering deformation of Bioglass® foams and is taken into account in the model. Qualitative comparison between the model predictions and experimental observations is presented, showing that the model is able to capture the complicated interplay between crystallization and viscous flow during the sintering process. © 2008 Acta Materialia Inc.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.atwosc
Keywords: Bioactive glass; Crystallization; Model; Sintering